Pengaruh Sistem Informasi Akuntansi dan Kompetensi Sumber Daya Manusia terhadap Kualitas Laporan Keuangan UMKM di Kabupaten Sragen - Mhelsye Jiran Valenticha; Fadjar Harimurti; Aris Eddy Sarwono; Sinta Putriana (Jurnal Ragam Pengabdian, 2026)
This study aims to examine the effect of accounting information systems and human resource competence on the quality of financial statements of Micro, Small, and Medium Enterprises (MSMEs) in Sragen Regency. The study employed a quantitative approach using a survey method. The population consisted of registered MSMEs in Sragen Regency, and a sample of 102 MSME owners was selected through purposive sampling. Primary data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics 26. The results indicate that the accounting information system has a positive and significant effect on the quality of financial statements, with a significance value of 0.031. Human resource competence also has a positive and significant effect on the quality of financial statements, with a significance value of less than 0.001. Simultaneously, both variables significantly affect the quality of financial statements, as indicated by an F-value of 121.667 and an Adjusted R Square of 0.705. These findings suggest that improving the quality of MSME financial statements requires optimizing the implementation of accounting information systems and enhancing human resource competence through education and training.